COMPARATIVE ANALYSIS OF CUSTOMER SATISFACTION BETWEEN CORNER BAKEY AND CAFE AND MM BAKERY IN BENGKALIS - Nabela Nabela; Adrian Irnanda Pratama (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2022)
This study aims to analyze differences in customer satisfaction between Corner Bakery and Cafe and MM Bakery, determine the factors that differentiate customer satisfaction between Corner Bakery and Cafe and MM Bakery. The type of research is comparative research with a quantitative approach. The population in this study was all consumers of Corner Bakery and Cafe and MM Bakery in Bengkalis. The number of samples in the study was 100 people. The data analysis used is descriptive statistics analysis. The dimensions used to measure customer satisfaction of the two bakery shops are product quality, service quality, emotional factors, and price. The study result that customer satisfaction of Corner Bakery and Cafe gets a better rating than MM Bakery based on dimensions of product quality, service quality, and emotional factors. The results also show that service quality is the most factor that differentiate customer satisfaction between Corner Bakery and Cafe and MM Bakery with a difference value around 0.21.